Central nervous system metastases as a cause of the first clinical symptoms of abreast cancer – a case report - Ziółkowska, Ewa; Łożyńska-Podhrebelna, Diana (Contemporary Oncology/Współczesna Onkologia, 2007)
Breast cancer is the most common malignant neoplasm among women. Brain metastases affect 20-40% of patients with breast cancer. It is difficult to properly treat these patients in view of the short overall survival – no longer than 10-16 months – after the operation and radiotherapy. We describe the treatment of a 47-year-old woman, whose first symptoms of breast cancer were caused by a single brain metastasis. Our individual therapeutic approach to the patient had led to her prolonged 3.5-year survival – in good general condition for most of this period. The treatment of patients with brain metastases is a very serious therapeutic problem. In the light of this case study we want to prove that selected patients should undergo multidisciplinary radical treatment of the disease and a very individual approach, even if it is different from the standard treatment.